CAGE20-7 Cruise Report: Sediment and water column analyses around flares at Norskebanken, Hinlopen and offshore Prins Karls Forland - Ferré, Bénédicte; Panieri, Giuliana; Kalenitchenko, Dimitri; Argentino, Claudio; Moser, Manuel; Dølven, Knut Ola; Sert, Muhammed Fatih; Stetzler, Marie; Savini, Alessandra; Lindgren, Matteus; Jones, Eleonore; de Groot, Tim; et al. (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
During the cruise CAGE 20-7 (November 2nd to 16th 2020), we observed and investigated a large active methane seepage area south from the Yermak plateau (Northern Svalbard), in particular to characterize the water column and the sediment near known flares in Norskebanken (Geissler et al., 2016). Some flares were targeted for gas composition, DNA and bubble size distribution. The combination of the R/V Kronprins Haakon and the ROV ÆGIR 6000 from the Norwegian Marine Robotics Laboratory at the University of Bergen allowed this investigation to happen in this rough environment, while collecting invaluable data from the ROV. The cruise may be known as: CAGE20_7